A unifying Bayesian framework accounting for spatiotemporal interferences with a deceleration tendency. (October 2021) - Chen, Youguo; Peng, Chunhua; Avitt, Andrew
Highlights: Deceleration tendency in the Kappa effect is driven by the Weber-Fechner law. Findings provide new insights into mechanisms of the spatiotemporal interferences. We combined a unifying Bayesian framework with a classical model of the Kappa effect. Abstract: Spatial and temporal levels of information processing interfere with each other. The Kappa effect is a well-known spatiotemporal interference in which the estimated time between two lights increases as the distance between them increases, showing a deceleration tendency. A classical model attributes this interference to constant speeds and predicts a linear relation, whereas a slowness model attributes the interference to slow speeds and proposes that the tendency is due to the uncertainty of stimuli locations. This study integrated a unifying Bayesian framework with the classical model and argued that this tendency is the result of the Weber–Fechner law. This hypothesis was tested via two time discrimination tasks that manipulated the uncertainty of stimuli locations and the distance between stimuli. Experiment 1 showed that the estimated time was not modulated by the uncertainty of the stimuli locations. Experiment 2 revealed that the behavioral predictions made by the Bayesian model on logarithmic scales were more accurate than those made by the linear model. Our results suggest that the deceleration tendency in the Kappa effect is the result of the Weber–Fechner law.